When Blue met Egg - Ward, Lindsay (Dial Books for Young Readers, 2012)
Blue spends months seeking the mother of the strange white egg that appeared in her nest one winter's day, enjoying New York City with her chilly friend, but as the weather grows warmer Egg becomes smaller.